2010
DOI: 10.1155/2010/807610
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Particle Surface Charge, Species, Concentration, and Dispersion Method on the Thermal Conductivity of Nanofluids

Abstract: The purpose of this experimental study is to evaluate the effects of particle species, surface charge, concentration, preparation technique, and base fluid on thermal transport capability of nanoparticle suspensions (nanofluids). The surface charge was varied by changing the pH value of the fluids. The alumina (Al 2 O 3 ) and copper oxide (CuO) nanoparticles were dispersed in deionized (DI) water and ethylene glycol (EG), respectively. The nanofluids were prepared using both bath-type and probe sonicator under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…Philip et al [13] studied the effect on thermal conductivity of low volume fraction of Fe3O4 nanofluids with particle size of 6 nm in different base fluids and found that the enhancement could approach 25%, as shown in Few studies show that the thermal conductivity enhancement of nanofluid is higher when the suspended nanoparticles have higher thermal conductivity [17,18]. Thermal conductivity studies done on Cu, CuO and Al 2 O 3 water, ethylene glycol and transformer oil based nanofluids show high thermal conductivity for metallic nanofluids compared to oxide nanoparticles [18].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Philip et al [13] studied the effect on thermal conductivity of low volume fraction of Fe3O4 nanofluids with particle size of 6 nm in different base fluids and found that the enhancement could approach 25%, as shown in Few studies show that the thermal conductivity enhancement of nanofluid is higher when the suspended nanoparticles have higher thermal conductivity [17,18]. Thermal conductivity studies done on Cu, CuO and Al 2 O 3 water, ethylene glycol and transformer oil based nanofluids show high thermal conductivity for metallic nanofluids compared to oxide nanoparticles [18].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 98%
“…Kwak et al [71] concluded that the large increase in thermal conductivity and viscosity at low nanoparticle volume fraction is an indication of aggregation effects. This has created interest in understanding the clustering phenomenon, and various studies have been conducted in this regard [72][73][74][75][76]. Interestingly, Prashaer et al [77] combined aggregation kinetics based on colloidal chemistry with the physics of thermal transport, and found that sedimentation is considerably visible due to aggregation, which negatively affects the thermal conductivity of nanofluids.…”
Section: Heat Transfer Mechanismmentioning
confidence: 99%
“…The dispersion of nanoparticles into conventional heat transfer fluids such as ethylene glycol, glycerol, engine oil, gear oil and water are of special interest due to their reported unique behaviors [5][6][7]. It is a known fact that conventional heat transfer fluids are characteristically poor in thermal properties [8,9]. Moreover, several studies [10][11][12][13] have shown that the addition of nanoparticles to these conventional heat transfer fluids increases their thermal conductivity, heat capacity, electrical conductivity and convective heat transfer coefficient when used in flow equipment.…”
Section: Introductionmentioning
confidence: 99%
“…Some major contributions have been made in the area of thermofluids engineering and these contributions have been reported in the literature. Gowda et al [8] showed that the enhancement in the thermal conductivity of nanofluids is dependent on nanoparticle type, nanoparticle volume fraction, nanoparticles surface charge, base fluid type and the overall energy input into the nanofluid preparation. Other researchers have shown that the thermal properties of nanofluid are also dependent on temperature and the particle size, the use of dispersant and type of dispersion assist mechanism used for the preparation [14][15][16].…”
Section: Introductionmentioning
confidence: 99%